Hubungan antara trait kepimpinan Guru Besar dengan komitmen kerja dalam kalangan guru sekolah berprestasi tinggi di daerah Johor Bahru - Badarudin, Mohd. Zulhida (2013)
The research intends to determine the relationship between headmaster’s leadership traits with teacher’s commitment in High Performance School (SBT) in the District of Johor Bahru, Johor. This research focused on two SBT schools in the district. A total of 150 teachers were selected as respondents for this study. The data were collected using questionnaire consisting of three sections, section A (Demography), section B (Headmasters trait leadership), and section C (Teachers work commitments). The collected data were than analyze using descriptive statistics (mean, and percentage) and inferential statistics (t-test, ANOVA, and correlation-Pearson). The findings explain the headmaster leadership traits, and the level of teachers’ commitment each recorded a mean average of 4.58 and 4.59. In addition,this study found that there was a moderate relationship between headmasters leadership traits with teachers work commitments with a correlation value of 0.602. The results showed no significant differences between teachers’ commitment based on gender with significant value 0.488. Based on the scheme of services does not show significant differences with the significant 0.294. Similarly, the races factor with significant value 0.452 and period of service with significant value 0.533. For teachers work commitments, continuance commitment is dominant with highest min value 4.64. Several suggestions are proposed for future research and as well as to help the top management of organization in education sectors.